Using near-infrared spectroscopy to determine moisture content, gel strength, and viscosity of gelatin. (June 2021) - Duthen, Simon; Levasseur-Garcia, Cecile; Kleiber, Didier; Violleau, Frédéric; Vaca-Garcia, Carlos; Tsuchikawa, Satoru; Delgado Raynaud, Christine; Daydé, Jean
Abstract: Gelatin is a natural biopolymer obtained by denaturation and partial hydrolysis of fibrous collagen, which is a fibrous protein present in the connective tissues of all species in the animal kingdom. Gelatin is used in many different industries, such as food, pharmaceuticals, photography, and cosmetics. The control of its physical properties is therefore of primary economic and technical importance for the gelatin industry, in particular because drying gelatin is the most expensive step in the manufacturing process and because customers demand products with well-controlled moisture content, gel strength, and viscosity. Consequently, a tool that provides rapid and nondestructive, real time analysis of gelatin would provide a definite competitive advantage. One such tool may be near-infrared (NIR) spectroscopy, which is a well-known analytical technique to determine the moisture content of complex matrices. We therefore use this technique to determine the moisture content, gel strength, and viscosity of 135 industrial gelatins. NIR spectra were acquired by using in reflectance mode a Fourier-transform NIR spectrometer with an integrating sphere to make a chemometric study of the industrial gelatins to determine the accuracy with which this technique can estimate moisture content, gel strength, and viscosity. The predictive accuracy for these parameters is quantified by using the ratio of performance of deviation (RPD), which gives 8.8, 3.7, and 2.1 in cross-validation, and 3.9, 1.8, and 1.9 in testing, respectively. Finally, we discuss the use of this technique in industrial conditions. Graphical abstract: Image 1 Highlights: Near infrared spectroscopy coupled with chemometrics methods was used to develop fast tool to analyze industrial gelatin. NIR spectra were acquired by using in reflectance mode a Fourier-transform NIR spectrometer with an integrating sphere. Results show that near infrared spectroscopy can be used to assess the physical properties of gelatin.